2014
DOI: 10.1111/dote.12165
|View full text |Cite
|
Sign up to set email alerts
|

Association of mu-opioid receptor expression with lymph node metastasis in esophageal squamous cell carcinoma

Abstract: The mu-opioid receptor (MOR), a membrane-bound G protein-coupled receptor, is the main target for opioids in the nervous system. MOR1 has been found in several types of cancer cells and reported to be involved in tumor progression and metastasis. However, the expression and clinical significance of MOR1 in esophageal squamous cell carcinoma (ESCC) remain unclear. In our study, the expression of MOR1 was confirmed in ESCC cell lines (KYSE180, KYSE150, and EC109) by Western blot. MOR1 was also detected on tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 39 publications
(80 reference statements)
3
39
0
Order By: Relevance
“…In the previous study, Mathew et al once described MOR is a novel regulator in lung cancer progression . In another study carried out by Zhang et al., cytoplasmic MOR1 expression was shown to be a high‐risk factor for lymph node metastasis of the patients. These hypotheses were further provided by our results, common to emphasize the specific involvement of MOR1 in the GC tumor progressive and metastatic procession.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In the previous study, Mathew et al once described MOR is a novel regulator in lung cancer progression . In another study carried out by Zhang et al., cytoplasmic MOR1 expression was shown to be a high‐risk factor for lymph node metastasis of the patients. These hypotheses were further provided by our results, common to emphasize the specific involvement of MOR1 in the GC tumor progressive and metastatic procession.…”
Section: Discussionmentioning
confidence: 98%
“…14 Previous studies showed that the cytoplasmic MOR1 expression may be a high-risk factor for lymph node metastasis of esophageal squamous cell carcinoma patients. 13 More recently, a study performed by Singleton et al suggested an increased mu-opioid receptor expression in the progression of metastatic lung cancer. 15 Moreover, stimulation of MOR1 in some tumor cells by opioids has been reported to influence tumor cell growth, migration and metastatic spread, indicating that opioids may have direct effects on cancer cell through activation of MOR1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of the μ receptor on cancer cells in murine models has been shown to increase the growth of lung cancer (Lennon et al, ), and decreasing μ receptor activity (using μ receptor small hairpin RNA mice or the opioid receptor antagonist methylnaltrexone) has been shown to reduce the growth of lung cancer (Mathew et al, ). Furthermore, μ receptor overexpression has been associated with the development of metastasis in patients with prostate, oesophageal and lung cancer (Zylla et al, ; Singleton et al, ; Zhang et al, ). Morphine influences the proliferation and survival of cancer cells via direct effects on tumour cell DNA cleavage, MAPK, Src, GRB2‐associated binding protein 1 (Gab‐1), PI3K, Akt and STAT3 signalling pathways (Mathew et al, ; Lennon et al, ; ).…”
Section: Opioids and The Immune Systemmentioning
confidence: 99%